The European Union after the Treaty of Lisbon - Ashiagbor, Diamond; Countouris, Nicola, 1975-; Lianos, Ioannis; Pech, Laurent (Cambridge : Cambridge, 2012)
"This volume of essays casts light on the shape and future direction of the EU in the wake of the Lisbon Treaty and highlights the incomplete nature of the reforms. Contributors analyse some of the most innovative and most controversial aspects of the Treaty, such as the role and nature of the EU Charter of Fundamental Rights and the relationship between the EU and the European Court of Human Rights. In addition, they reflect on the ongoing economic and financial crisis in the Euro area, which has forced the EU Member States to re-open negotiations and update a number of aspects of the Lisbon 'settlement'. Together, the essays provide a variety of insights into some of the most crucial innovations introduced by the Lisbon Treaty and in the context of the adoption of the new European Financial Stability Mechanism"--
"To remain masters of their destiny, six European countries agreed to establish among themselves a European Economic Community (EEC) in 1957. To remain masters of their creation, the national governments devised a rather unique institutional system whose fundamental features can only be amended by unanimity. In fact, to enter into force, any amendment made to the European founding treaties has always required ratification by all the Member States in accordance with their respective constitutional requirements. Remarkably, this demanding procedural requirement has not precluded a spectacular 'widening' of the membership of what is now known as the European Union (EU) as well as a considerable 'deepening' of the competences conferred on the EU by its Member States. Indeed, from an organisation originally consisting of six countries with a narrow focus on economic matters, the EU has grown beyond recognition. Its 27 Member States now pursue an extensive and diverse set of objectives amongst which one may mention the promotion of balanced and sustainable development of economic activities, the implementation of a common foreign and security policy and the tackling of cross-border crime. In order to effectively pursue these objectives, the EU has also gradually gained the power to legislate in the areas of monetary policy, social policy, environment, consumer protection, asylum and immigration, amongst other things"--
Machine generated contents note: Introduction Diamond Ashiagbor, Nicola Countouris and Ioannis Lianos; 1. The institutional development of the EU post-Lisbon: a case of plus ça change...? Laurent Pech; 2. Competence after Lisbon: the elusive search for bright lines Takis Tridimas; 3. The Charter, the ECJ and national courts P. P. Craig; 4. Accession of the EU to the ECHR: who would be responsible in Strasbourg? Tobias Lock; 5. EU citizenship after Lisbon Niamh Nic Shuibhne; 6. The law and politics of migration and asylum: the Lisbon Treaty and the EU Sabina Anne Espinoza and Claude Moraes; 7. The European Union's Common Foreign and Security Policy after Lisbon Panos Koutrakos; 8. The European Ombudsman and good administration post-Lisbon P. Nikiforos Diamandouros, European Ombudsman; 9. European contract law after Lisbon Lucinda Miller; 10. Competition law in the European Union after the Treaty of Lisbon Ioannis Lianos; 11. The unexpected revision of the Lisbon Treaty and the establishment of a European Stability Mechanism Jean-Victor Louis.
Includes bibliographical references and index.
Keywords: European Union -- Constitution; Treaty on European Union -- (1992 February 7). -- (2007 December 13); Law -- European Union countries; LAW / International